Field induced metastable ferroelectric phase in Pb0.97La0.03(Zr0.90Ti0.10)0.9925O3 ceramics. Issue 4 (April 2018) - Ciuchi, I.V.; Chung, C.C.; Fancher, C.M.; Capiani, C.; Jones, J.L.; Mitoseriu, L.; Galassi, C.
Abstract: Pb0.97 La0.03 (Zr0.9 Ti0.1 )0.9925 O3 (PLZT 3/90/10) ceramics prepared by solid-state reaction with the compositions near the antiferroelectric/ferroelectric (FE/AFE) phase boundary were studied. From the polarization–electric field P(E) dependence and ex situ X-ray study, an irreversible electric field induced AFE-to-FE phase transition is verified at room temperature. Dielectric and in situ temperature dependent X-ray analysis evidence that the phase transition sequence in PLZT 3/90/10-based ceramics can be readily altered by poling. A first order antiferroelectric-paraelectric (AFE-to-PE) transition occurred at ∼190 °C in virgin sample and at ∼180 °C in poled sample. In addition, a FE-to-AFE transition occurs in the poled ceramic at much lower temperatures (∼120 °C) with respect to the Curie range (∼190 °C). The temperature-induced FE-to-AFE transition is diffuse and takes place in a broad temperature range of 72–135 °C. The recovery of AFE is accompanied by an enhancement in the piezoelectric properties.